Do women with a history of breast cancer recommend risk-based breast cancer screening? An in-depth interview study - Zi Lin Lim; Freda Giam; Renee Ying Xuan Wong; Jonathan Jun Kit Liow; Keri McCrickerd; Keri McCrickerd; Jingmei Li; Jingmei Li; Jingmei Li (Frontiers in Psychology)
ObjectivesPersonalizing screening recommendations could enhance efficiency, support timely detection, and optimize resource use. This study explores women’s perceptions of the facilitators and barriers to current screening guidelines and the implementation of risk-based screening (RBS) for breast cancer in Singapore.MethodsIndividual semi-structured interviews were conducted with 11 women aged 21 and above with a history of breast cancer. Data coding and thematic analysis were guided by the Health Belief Model (HBM).ResultsFive themes were identified and mapped to the Health Belief Model (HBM): (1) Knowledge and beliefs, (2) Access to mammography screening, (3) Social influences, (4) Healthcare delivery, and (5) Needs and preferences for RBS implementation. Key barriers to screening adherence included low perceived susceptibility, cost concerns, and accessibility issues. Factors that could improve adherence included social influences promoting breast health awareness, reminders from trusted healthcare professionals (HCP), and confidence in affording screening and treatment. Participants were generally receptive to RBS and valued personalized recommendations, but concerns were raised about risk prediction accuracy, insurance implications, and potential negative reactions to risk results.ConclusionThis study identifies challenges and enablers for enhancing breast screening in Singapore, based on the experiences of breast cancer survivors. Participants supported RBS for routine screening. Successful RBS implementation requires improved health literacy, HCP engagement, and accessible healthcare. Women’s acceptance will rely on research to refine prediction accuracy and communication of risk results.